Upper stratosphere-mesosphere-lower thermosphere perturbations during the formation of the Arctic polar night jet in 2019–2020 - Lukianova, R. (Renata); Kozlovsky, A. (Alexander); Lester, M. (Mark) (American Geophysical Union, 2021)
Abstract Thermal and dynamic perturbations in the polar upper stratospheric/mesosphere-lower thermosphere in the Arctic winter of 2019–2020 as measured by a meteor radar at 67°N, Aura Microwave Limb Sounder and reanalysis are presented. The most severe disturbances occur from late December to mid-January, while the rest of the winter is relatively stable. Mesospheric winds are dominated by several impulsive increases in the zonal component, an abrupt descent of the wind core and alternating north- and south-ward flow with a period of half a month. Reduced temperature at 90 km height accompanied by thermal inversions is observed in association with upper stratosphere/lower mesosphere warming in the eastern hemisphere. The warming trend is interrupted by a strong cooling in the entire stratosphere-mesosphere. The upper middle atmosphere appears considerably stratified. High “walls” surround the vortex that is favorable for its stability.